2017
DOI: 10.1039/c7cp04357k
|View full text |Cite
|
Sign up to set email alerts
|

Role of intermolecular charge delocalization and its dimensionality in efficient band-like electron transport in crystalline 2,5-difluoro-7,7,8,8-tetracyanoquinodimethane (F2-TCNQ)

Abstract: Theoretical understanding of charge transport in organic semiconductors is exclusively important for organic electronics, but still remains a subject of debate. The recently discovered record-high band-like electron mobility in single crystals of 2,5-difluoro-7,7,8,8-tetracyanoquinodimethane (F-TCNQ) is challenging from the theoretical viewpoint. First, the very small size of the F-TCNQ molecule implies high reorganization energy that seems incompatible with efficient charge transport. Second, it is not clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Among the different derivatives, it is reported that F 2 -TCNQ shows much higher electron mobility in Organic Field Effect Transistors (OFETs) than TCNQ or F 4 -TCNQ, up to 25 cm 2 V À1 s À1 compared with $ 0.1 cm 2 V À1 s À1 . High band-like electron mobility observed in F 2 -TCNQ was attributed to the presence of planar molecular packing and one molecule in the primitive unit cell (Chernyshov et al, 2017;Krupskaya et al, 2015;Sosorev, 2017). While the molecular packing of these molecules has been discussed previously, the aim of this study was to perform an in-depth quantitative and qualitative investigation into the unique structural and molecular features in this class of molecules.…”
Section: Introductionmentioning
confidence: 94%
“…Among the different derivatives, it is reported that F 2 -TCNQ shows much higher electron mobility in Organic Field Effect Transistors (OFETs) than TCNQ or F 4 -TCNQ, up to 25 cm 2 V À1 s À1 compared with $ 0.1 cm 2 V À1 s À1 . High band-like electron mobility observed in F 2 -TCNQ was attributed to the presence of planar molecular packing and one molecule in the primitive unit cell (Chernyshov et al, 2017;Krupskaya et al, 2015;Sosorev, 2017). While the molecular packing of these molecules has been discussed previously, the aim of this study was to perform an in-depth quantitative and qualitative investigation into the unique structural and molecular features in this class of molecules.…”
Section: Introductionmentioning
confidence: 94%
“…In the singlet multiplicity state of the dimer in the gas phase, the coupling between the SOMO orbitals, estimated from the energy splitting is 0.68 eV (see Table ). This is significantly higher coupling that known for the TCNQ crystals with different mutual orientation of the TCNQ monomers in the crystal, what suggests efficient electron transport properties of the TCNQ in the material.…”
Section: Figurementioning
confidence: 73%
“…Also, we intentionally used a rather simple charge transport model based on the Marcus theory, although charge transport in nucleic acids can be more complex and still remains a subject of debates [40]. Possible charge delocalization between the sites that could decrease the effective reorganization energies [51][52][53]43] was neglected. Moreover, the very site energies (ionization potentials of nucleotides) can be dependent on charge delocalization [54] and hence on J. Ionic conductivity, which can be coupled to the electronic charge transport discussed herein [55], is also accounted for simply at the level of counterions added to tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For the calculation of reorganization energies, λab, the nucleotides were substituted by nucleobases with hydrogens instead of ribose moiety. The λab values were approximated by their internal (intramolecular) parts and calculated according to the standard adiabatic potentials (four-point) scheme [44,53]. Specifically, λab was calculated as λab = λb,ch + λa,dis = (ENb * -ENb) + (ECa * -ECa), where ENb and ENb * are the energies of the neutral state of site b in its optimized geometry and in the optimized geometry of the charged state, respectively, while ECa and ECa * are the energies of the charged state of site a in its optimized geometry and in the geometry of the neutral state, respectively.…”
Section: Methodsmentioning
confidence: 99%